2021
DOI: 10.2320/matertrans.m-m2020872
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Refining by Solidification from Liquid Si–Zn Alloy and Floating Zone Method

Abstract: This study evaluated the refining ability of a proposed production process for solar-grade silicon utilizing the electrolytic reduction of SiO 2 on a liquid zinc electrode in molten salt. The distribution behaviors of impurity elements during the precipitation of solid silicon from a liquid SiZn alloy were studied by thermodynamic calculations at 923 K. In the precipitation experiment, silicon granules were recovered from a liquid SiZn alloy, which was prepared from metallurgical-grade silicon. The impurity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Here, the deposition mechanism of crystalline Si is discussed in terms of crystal size. In previous reports of Si precipitation by decreasing the temperature of liquid Si-Zn alloys, the precipitated Si grains became smaller at a higher cooling rate (18). Even at the temperature decreasing rate of 20 K h −1 , only Si grains smaller than 1 mm were obtained (18).…”
Section: Deposition Of Si By Potentiostatic Electrolysismentioning
confidence: 78%
“…Here, the deposition mechanism of crystalline Si is discussed in terms of crystal size. In previous reports of Si precipitation by decreasing the temperature of liquid Si-Zn alloys, the precipitated Si grains became smaller at a higher cooling rate (18). Even at the temperature decreasing rate of 20 K h −1 , only Si grains smaller than 1 mm were obtained (18).…”
Section: Deposition Of Si By Potentiostatic Electrolysismentioning
confidence: 78%
“…Previous reports on Si precipitation showed that decreasing the temperature of liquid Si-Zn alloys decreases the size of the precipitated Si grains at a higher cooling rate. 38 Even at the temperature-decreasing rate of 20 K h −1 , only Si grains smaller than 1 mm were obtained. 38 In the present study, the Si-Zn liquid alloy was cooled through natural cooling, and the temperaturedecreasing rate was extremely high (approximately 230 K s −1 ).…”
Section: + ( ) + → − ( ) [ ]mentioning
confidence: 95%
“…38 Even at the temperature-decreasing rate of 20 K h −1 , only Si grains smaller than 1 mm were obtained. 38 In the present study, the Si-Zn liquid alloy was cooled through natural cooling, and the temperaturedecreasing rate was extremely high (approximately 230 K s −1 ). Therefore, Si powders with small grain sizes could have been deposited during natural cooling.…”
Section: + ( ) + → − ( ) [ ]mentioning
confidence: 95%
See 1 more Smart Citation